Association Between Formative Assessment and Academic Performance for Undergraduate Medical Students in a Chinese Clinical Skills Training Course - Zhu, Tianxin (Med Sci Monit, 2021)
BACKGROUND: Previous research suggests that formative assessment (FA) enhances learning outcomes, but few studies have evaluated its impact on clinical skills training in China. We conducted this study in a clinical skills integral curriculum to further explore the educational value of FA. MATERIAL/METHODS: Sixty undergraduates from the Second Clinical Medical School of the Southern Medical University in 2016 were selected as the experimental group (consecutive FA), and 50 undergraduates in 2015 were selected as the control term (only final summative assessment, SA). Undergraduates in the FA group completed the after-class questionnaire at each lesson. Teachers, teaching content, assessment objectives, and topics are the same in both groups. RESULTS: The results of single-factor covariance (ANCOVA) analysis and Cochran-Mantel-Haenszel (CMH) analysis demonstrated that students of the FA group obtained better performance and higher success rates in summative examination than in the SA group. The students with relatively poor grades benefited more from FA, while the performance of students with higher grades was similar between the FA group and SA group. According to the results of questionnaire for students, the satisfaction of students with the course increased gradually, from 84.4% to 93.0%. CONCLUSIONS: Proper use of FA is associated with better learning outcomes for students, especially for those with poorer grades. Our results, together with previous research, indicated that the use of FA may be of great benefit to students’ academic performance and satisfaction with the clinical skills training curriculum.